Comparison of deep and moderate neuromuscular blockade in microwave ablation of liver tumours: a randomized-controlled clinical trial - Pui San Loh (Nature Portfolio, 2021)
Abstract Microwave ablation (MWA) is gaining popularity for the treatment of small primary hepatocellular carcinoma and metastatic lesions especially if patients are not candidates for surgical resection. Deep neuromuscular blockade (DMB) is perceived to improve surgical working conditions compared to moderate neuromuscular blockade (MMB) but no studies have examined the same benefits in MWA of liver tumours. This study aimed to compare the clinical outcomes of DMB and MMB in MWA of liver tumours in terms of liver excursion, performance scores by the interventional radiologists and patients, requirements of additional muscle relaxants and complications. 50 patients were recruited and 45 patients (22 in MMB group, 23 in DMB group) completed the study. The mean liver excursion for the MMB group (1.42 ± 1.83 mm) was significantly higher than the DMB group (0.26 ± 0.38 mm) (p = 0.001). The mean Leiden-Surgical Rating Scale (L-SRS) rated by the two interventional radiologists were 4.5 ± 0.59 and 3.6 ± 0.85 for the DMB and MMB groups, respectively (p = 0.01). There was also statistically significant difference on patient satisfaction scores (0–10: Extremely Dissatisfied–Extremely Satisfied) between DMB (8.74 ± 1.1) and MMB (7.86 ± 1.25) groups (p = 0.01). 5 patients from MMB group and none from DMB group required bolus relaxant during the MWA procedure. Adverse events were also noted to be more severe in the MMB group. In conclusion, DMB significantly reduced liver excursion and movement leading to improved accuracy, safety and success in ablating liver tumour.